Cephalometric Morphology of Turkish Children with Class II Malocclusion - Bengisu Akarsu; İlken Kocadereli (Galenos Yayinevi, 2010)
Aim:To investigate the morphology of Class II malocclusion in Turkish children, to compare with Class I malocclusion sample and to identify possible sex differences.Subjects and Methods:Lateral cephalometric radiographs of 100 Turkish children with Class II malocclusion and 100 Turkish children with Class I malocclusion taken in centric occlusion were selected. The mean age of the patients were 12.2±2.1 years for Class II group and 12.3±2.4 years for Class I group. A cephalometric software system was used to perform lateral cephalometric evaluation. Independent-samples t test and Mann Whitney-U test were used for statistical analysis.Results:SNB Angle, ANB Angle, Facial Depth Angle, Condylion-Gnathion Length, Corpus Length, Convexity, Lower Lip to Esthetic Plane Distance, Overjet and Overbite showed statistically significant differences between the Class II and Class I children. The mandibular incisors were more proclined in Class II group. There was no significant difference in the vertical growth pattern between the groups. In Class I group, FMA Angle, Lower Facial Height Angle, Corpus Length, Condylion-Gnathion Length, Condylion-A Length, Anterior Facial Height and Posterior Facial Height were found to be smaller in females. In Class II group, SNA Angle, SNB Angle, Maxillary Depth, L1-NB Angle and U1-SN Angle were found to be smaller in males.Conclusion:The results of the study showed that the majority of the Class II pattern in Turkish patients was due to mandibular retrusion, and on average the children had dolichofacial growth pattern.